1989
DOI: 10.1530/jrf.0.0850043
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ejaculation frequency on semen characteristics in chimpanzees (Pan troglodytes)

Abstract: Summary. Semen samples were obtained by masturbation from 6 chimpanzees and the spontaneously liquefied fraction and the remaining coagulum were studied separately. When semen was collected once or twice a week, large intra-individual variations were observed for all measures. The liquefied fraction represented 26\m=.\5 \ m=+-\ 3\m=.\2% (weighted mean \m=+-\ s.d.) of the total ejaculate but contained 51\m=.\3\m=+-\ 3\m=.\8%of all emitted spermatozoa. Fructose concentration was higher in the coagulum than in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 31 publications
4
32
0
1
Order By: Relevance
“…Although our results indicate that females may have some control over male ejaculation, they apparently do not use this to select certain males as mating (ejaculation) partners. Since male vertebrates are known to allocate their sperm between matings (Packer & Pusey 1982;Wedell et al 2002) and since high frequencies of ejaculations can lead to a decrease in sperm quality (Synott et al 1981;Marson et al 1989;Preston et al 2001), calling may enable females to (at least partially) influence the allocation of this limited resource. Whether or not cryptic female choice mechanisms operate to influence sperm transport or selection at a post-ejaculatory level (Birkhead & Pizzari 2002) in this species is not yet known.…”
Section: Discussionmentioning
confidence: 99%
“…Although our results indicate that females may have some control over male ejaculation, they apparently do not use this to select certain males as mating (ejaculation) partners. Since male vertebrates are known to allocate their sperm between matings (Packer & Pusey 1982;Wedell et al 2002) and since high frequencies of ejaculations can lead to a decrease in sperm quality (Synott et al 1981;Marson et al 1989;Preston et al 2001), calling may enable females to (at least partially) influence the allocation of this limited resource. Whether or not cryptic female choice mechanisms operate to influence sperm transport or selection at a post-ejaculatory level (Birkhead & Pizzari 2002) in this species is not yet known.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it may be possible that sperm reserves of the dominant males are depleted by frequent ejaculation as in humans [Freund, 1963;Levin et al, 1986]. In a study of adolescent common chimpanzees, it was found that repeated ejaculation had an adverse effect on sperm quality; however, the effect was less pronounced than observed in humans [Marson et al, 1989]. Again, nothing is known about the effect of frequent ejaculation in bonobos or about its relation to age or social rank.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because the sperm of the dominant male is limited (Dewsbury 1982, Marson et al 1989, Wedell et al 2002, Preston et al 2003 Female primates show situation-dependent flexibility in mating behavior that may act to reduce the risk of sexually selected infanticide by nonsire males (Hrdy 1979, Hrdy & Whitten 1987, Smuts & Smuts 1993. For example, where group takeover by a new male leads to a high risk of infanticide for infants sired by a previous male, females that are already pregnant solicit the new male for mating ("pseudo-oestrous", Table 15.1), resulting in paternity confusion and reduction in the risk of infanticide.…”
Section: Harassment and Avoidancementioning
confidence: 99%